Measuring and understanding the attitudes of Australian gay and bisexual men towards biomedical HIV prevention using cross-sectional data and factor analyses. (21st November 2017) - Wilkinson, Anna L; Draper, Bridget L; Pedrana, Alisa E; Asselin, Jason; Holt, Martin; Hellard, Margaret E; Stoové, Mark
Abstract : Introduction: Contemporary responses to HIV embrace biomedical prevention, particularly treatment as prevention (TasP) and pre-exposure prophylaxis (PrEP). However, large-scale implementation of biomedical prevention should be ideally preceded by assessments of their community acceptability. We aimed to understand contemporary attitudes of gay and bisexual men (GBM) in Australia towards biomedical-based HIV prevention and propose a framework for their measurement and ongoing monitoring. Methods: A cross-sectional, online survey of GBM ≥18 years has been conducted annually in Victoria, Australia, since 2008. In 2016, 35 attitudinal items on biomedical HIV prevention were added. Items were scored on five-point Likert scales. We used principal factor analysis to identify key constructs related to GBM's attitudes to biomedical HIV prevention and use these to characterise levels of support for TasP and PrEP. Results: A total of 462 HIV-negative or HIV-status-unknown men, not using PrEP, provided valid responses for all 35 attitudinal items. We extracted four distinct and interpretable factors we named: 'Confidence in PrEP', 'Judicious approach to PrEP', 'Treatment as prevention optimism' and 'Support for early treatment'. High levels of agreement were seen across PrEP-related items; 77.9% of men agreed that PrEP prevented HIV acquisition and 83.6% of men agreed that users were protecting themselves. However, the agreement levels for HIV TasP items were considerably lower, with <20% of men agreeing treatment (undetectable viral load) reduced HIV transmission risk. Conclusions: Better understanding of community attitudes is crucial for shaping policy and informing initiatives that aim to improve knowledge, acceptance and uptake of biomedical prevention. Our analyses suggest confidence in, acceptability of and community support for PrEP among GBM. However, strategies to address scepticism towards HIV treatment when used for prevention may be needed to optimise combination biomedical HIV prevention.